2005
DOI: 10.1212/01.wnl.0000173837.82820.9f
|View full text |Cite
|
Sign up to set email alerts
|

Frontotemporal dementia progresses to death faster than Alzheimer disease

Abstract: Frontotemporal lobar degeneration progresses more rapidly than Alzheimer disease, and the fastest-progressing cases are those with the frontotemporal dementia clinical subtype, coexisting motor neuron disease, or tau-negative neuropathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
189
10
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(220 citation statements)
references
References 35 publications
14
189
10
4
Order By: Relevance
“…The lack of correlation might reflect weaknesses in diagnostic definitions, or could be due to the relatively small sample number. Earlier studies of FTD survival show a median survival time of three years from clinical presentation (15). In this study, rapid progression was defined as distinct frontal and/or temporal atrophy in a brain MRI after a maximum three years of disease duration, and survival time was not included in the definition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of correlation might reflect weaknesses in diagnostic definitions, or could be due to the relatively small sample number. Earlier studies of FTD survival show a median survival time of three years from clinical presentation (15). In this study, rapid progression was defined as distinct frontal and/or temporal atrophy in a brain MRI after a maximum three years of disease duration, and survival time was not included in the definition.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been suggested that FTD is an aggressive disease with a significantly shorter survival time than Alzheimer's disease (AD) (15), a more benign variant with a lack of gross atrophy on structural imaging or post-mortem macroscopy has been identified (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Most research efforts have concentrated on defining typical neuroimaging features of FTD cross-sectionally, but less is known about its clinical Roberson et al, 2005) and anatomical (Gregory et al, 1999;Chan et al, 2001;Whitwell et al, 2004) evolution over time.…”
Section: Introductionmentioning
confidence: 99%
“…1 The differential diagnosis for FTLD and AD has a potential impact for treatment and prognosis. [2][3][4] Currently available drugs such as the acetylcholinesterase (AchE) inhibitor for treating AD are often ineffective for the treatment of FTLD. 5 Furthermore, FTLD often shares clinical features with AD, whereas AD is often associated with FTLD clinical syndromes.…”
mentioning
confidence: 99%